Study of travel time and delay in North Klang / Nur Hafizah Md Salleh - Md Salleh, Nur Hafizah (2007)
Travel lime is the time required to traverse from one point to the point of interest while delay is the time lost by traffic due to traffic frictions and traffic control devices. Travel-time and delay information could he applied in various fields. This information will be used by the engineer, planner and analysts to determine the effectiveness of transportation system. The objective of this research is to obtain the duration to transverse from the starting point to the end point along the study routes in North Klang. The purpose of this study is to determine the location, duration and causes of delay occurred. It w ill also used to quantify the traffic movement din ing of peak and off-peak hour period. This research was done using the average speed vehicle method. In this research, the travel time and delay will be recorded, and the travel time is expected to increase due to the increasing number of vehicles. The travel time and delay during the off peak is done to enable in making comparison with the travel time data determined during peak hour.